Magnetocaloric and thermoelectric properties of the perovskite LaMnO3 material: A DFT study and Monte Carlo technique. (2nd November 2021) - Tahiri, N.; Dahbi, S.; Dani, I.; El Bounagui, O.; Ez-Zahraouy, H.
ABSTRACT: To optimize the performance of the magnetocaloric effect in the perovskite LaMnO3 compound, it is important to study the electronic structure, magnetic, magnetocaloric, and thermoelectric properties of this material. Using the first-principles method, the magnetic moment, the coupling interactions between magnetic atoms Mn-Mn ( J M n − M n 1, J M n − M n 2 ), and the crystal field are calculated. The magnetic properties of the perovskite LaMnO3 material are determined by using the Monte Carlo simulation. It is shown that, at low temperature, the magnetization value is in good agreement with the corresponding spin at T ∼ 0.0 K . In addition, the obtained Curie temperature ( T C = 145 K ) is in good agreement with the experimental value. The magnetic entropy ( Δ S m m a x ), the adiabatic temperature ( Δ T a ), and the relative cooling power ( R C P ) values are 2.991 J / k g . K, 4.25 K, 182.984 J / K g, respectively. Finally, the thermoelectric properties are discussed. This material is applicable for magnetic refrigeration at Curie temperature.